2017
DOI: 10.4236/ijcm.2017.811053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pregnancy Outcomes of High-Quality D5- and D6-Blastocyst Transfer in Hormone-Replacement Frozen-Thawed Cycles

Abstract: This study aimed to assess pregnancy outcomes after high-quality D5-and D6-blastocyst transfer in frozen cycles of in vitro fertilization and embryo transfer and to further evaluate whether there was a difference in blastocyst development potentials with different developmental speeds and in pregnancy outcomes. A retrospective analysis was conducted to analyze 247 frozen cycles in our center from September 2015 to July 2017, which were divided into two groups: a D5-FET group with 193 cycles of D5-blastocyst tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…A consistent conclusion has not yet been reached in this ongoing debate. Some authors suggest better clinical outcomes for D5 embryos [40,41], whereas other studies find no differences associated with the embryo transfer day [42][43][44]. A common explanation for lower pregnancy outcomes for D6 transfer is the discordance between the patient endometrium and the embryo stage.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent conclusion has not yet been reached in this ongoing debate. Some authors suggest better clinical outcomes for D5 embryos [40,41], whereas other studies find no differences associated with the embryo transfer day [42][43][44]. A common explanation for lower pregnancy outcomes for D6 transfer is the discordance between the patient endometrium and the embryo stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that day 5 blastocysts transfer achieves higher pregnancy rates than day 6 blastocysts transfer, suggesting the improved viability for faster-developing embryos [3][4][5]. In this study, the next generation sequencing (NGS)-based PGT-A results were used to compare the ploidy status and clinical outcomes between day 5 blastocysts and day 6 blastocysts.…”
Section: Introductionmentioning
confidence: 99%